Reduction‐Driven 3D to 2D Transformation of Cu Nanoparticles (Small 7/2022). Issue 7 (17th February 2022) - Matte, Lívia P.; Thill, Alisson S.; Lobato, Francielli O.; Novôa, Matheus T.; Muniz, André R.; Poletto, Fernanda; Bernardi, Fabiano
Abstract : Metal–Support Interactions The enhancement of the metal/metal oxide interaction is beneficial for a wide range of applications at the nanoscale. Besides, in catalytic applications, the shape of the metallic nanoparticles plays a pivotal role in the catalytic performance. In article number 2106583, Fabiano Bernardi and co‐workers show the existence of a 3D to 2D transformation of Cu nanoparticles supported on CeO2 when exposed to a CO atmosphere at 400 °C. The transformation changes the shape of the Cu nanoparticles and improves the metal/metal oxide interaction.